The Implementation of Individual Islamic Counseling in Developing the Spiritual Intelligence of Client 'X' - Bin Solihin, Shahzwanny; Jannati, Zhila; Janare Putra, Bela (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2025)
This research is titled The Implementation of Individual Counseling Based on Islamic Principles in Developing the Spiritual Intelligence of Client' X'. The background of this study lies in the importance of developing spiritual intelligence for converts to Islam (muallaf) who are undergoing a transitional phase in their faith, especially in facing emotional, social, and spiritual challenges. Client 'X' is a 40-year-old man who recently embraced Islam and is experiencing various crises, such as family conflict, psychological pressure, and doubts about living his new life as a Muslim. This study explores how implementing individual counseling based on Islamic principles can develop the spiritual intelligence of client 'X'. This research uses a qualitative approach with a phenomenological method. Data were collected through participant observation, in-depth interviews, and documentation. The findings indicate that individual counseling based on Islamic values, integrating teachings from the Qur'an and Hadith, is highly effective in enhancing the client's spiritual intelligence. The client developed greater self-awareness, emotional regulation, a sense of life purpose, and attitudes of patience, empathy, and acceptance of Allah's decree. Spiritual activities such as prayer and dhikr became more structured and meaningful in the client's daily life. This study concludes that implementing Islamic-based individual counseling positively assists converts in facing life's challenges and developing their spiritual intelligence. The results can serve as a reference for counselors, educators, and Islamic guidance practitioners in providing more holistic and meaningful support to converts.